Role of Physiotherapy and Nursing in Multidisciplinary Team in Stroke Rehabilitation: Examining the Role of Physiotherapy and Nursing in Subacute Post-Stroke Rehabilitation (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Physiotherapist and Nurses are the largest professional workforce working with stroke survivors. However, the study of physiotherapist and nurses’ role in subacute post-stroke rehabilitation is sparse. The objective of this study was to describe the experienced roles of physiotherapist and nurses during subacute rehabilitation of stroke survivors. Physiotherapist and Nurses integrate rehabilitation principles in routine care thus make an important contribution to post-stroke rehabilitation in subacute settings. However, physiotherapist and nurses lack training in post-stroke rehabilitation, which limited their roles and functions in the subacute rehabilitation of patients with stroke.